2015
DOI: 10.1007/s00442-015-3392-5
|View full text |Cite
|
Sign up to set email alerts
|

Foraging competition in larger groups overrides harassment avoidance benefits in female reindeer (Rangifer tarandus)

Abstract: Male harassment toward females during the breeding season may have a negative effect on their reproductive success by disturbing their foraging activity, thereby inducing somatic costs. Accordingly, it is predicted that females will choose mates based on their ability to provide protection or will aggregate into large groups to dilute per capita harassment level. Conversely, increasing group size may also lead to a decrease in foraging activity by increasing foraging competition, but this effect has rarely bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…If multiple mating is primarily driven by male harassment, we would expect increased instance of multiple mating at higher male percent composition. An increased sex ratio should increase the opportunity for harassment by increasing the number of potential harassing males per female, and possibly by providing an environment that favors male targeting of specific females ( Uccheddu et al 2015 ). Indeed, previous studies have indicated that greater percentage of males limits the ability of high-ranking males to effectively monopolize females by increasing intraspecific competition ( Reale et al 1996 ; Clutton-Brock et al 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…If multiple mating is primarily driven by male harassment, we would expect increased instance of multiple mating at higher male percent composition. An increased sex ratio should increase the opportunity for harassment by increasing the number of potential harassing males per female, and possibly by providing an environment that favors male targeting of specific females ( Uccheddu et al 2015 ). Indeed, previous studies have indicated that greater percentage of males limits the ability of high-ranking males to effectively monopolize females by increasing intraspecific competition ( Reale et al 1996 ; Clutton-Brock et al 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Risk of predation is hypothesized to affect group size of ungulates via benefits of increased group size in open‐land species that accrue because of more eyes, ears, and noses with which to detect predators at distances that make successful pursuits unlikely (Roberts, 1996). Costs related to competition, however, may be associated with large groups (Uccheddu, Body, Weladji, Holand, & Nieminen, 2015). For forest‐dwelling ungulates, where avoidance of detection is thought to be the primary antipredator strategy, benefits ostensibly ensue from being solitary or living in small groups (Hirth & McCullough, 1977).…”
Section: Factors Influencing Gregariousnessmentioning
confidence: 99%
“…By joining a large group, foragers should benefit not only from a decrease in predation risk (e.g., dilution effect [11], collective detection [12]), but also from an increase in social information about spatio-temporal patterns in resource availability [1315]. These benefits, however, can be shadowed by faster resource depletion, higher exploitative and interference competition [1619], and slower collective movements that are typical of larger groups [20]. Overall, foragers in larger groups should experience a faster decrease in food intake rate (i.e., faster patch depression, sensu [21]) and, therefore, have to rely more often upon an extensive search mode, which might be less effective because of the slower movement of large groups.…”
Section: Introductionmentioning
confidence: 99%